Vaccine strategies for lowering LDL by immunization against proprotein convertase subtilisin/kexin type 9. Issue 4 (August 2016) - Chackerian, Bryce; Remaley, Alan
Abstract : Purpose of review: mAbs targeting proprotein convertase subtilisin/kexin type 9 (PCSK9) have the potential to become groundbreaking therapies for the treatment of hypercholesterolemia. However, one major drawback of mAb-based therapy for a chronic condition like dyslipidemia is its relatively high cost. This review summarizes two recent studies describing novel vaccine approaches for lowering LDL-cholesterol by active immunization against PCSK9. Recent findings: PCSK9 is a plasma protein secreted by the liver that controls cholesterol homeostasis by enhancing endosomal and lysosomal degradation of the LDL receptor. Two PCSK9 inhibitory mAbs (evolocumab and alirocumab) have recently been approved by the Food and Drug Administration and a third mAb (bococizumab) is in late stage clinical trials. Treatment with PCSK9 mAbs, in combination with statins, reduces LDL-cholesterol levels by as much as 40–60%. As an alternative to mAbs, there have been two recent studies describing the development of vaccines that target PCSK9. These studies have shown that PCSK9 vaccines can effectively induce high-titer antibody responses that reduce proatherogenic lipoproteins in animal models. Summary: A PCSK9 vaccine-based approach could serve as a more widely applicable and a more cost-effective approach than mAb therapy for controlling hypercholesteremia and associated cardiovascular disease.